Childhood experiences and housing insecurity in adulthood: The salience of childhood emotional abuse. (November 2017) - Curry, Susanna R.
Abstract: The majority of recent research and interventions related to childhood experiences and young adult housing challenges has been focused on the role of foster care involvement. However, we know much less about how a wider range of childhood experiences, such as maltreatment, relate to adult economic and housing outcomes. Informed by the Stress Process Model, the present study uses data from 11, 764 individuals from Waves 1, 3, and 4 in-home surveys of the National Longitudinal Study of Adolescent to Adult Health. Bivariate tests and logistic regressions explored whether a history of foster care involvement, running away before age 18, being kicked out of home, or frequency of incidents of child maltreatment (physical, emotional, or sexual abuse) prior to age 18 are related to housing insecurity in adulthood, measured by inability to pay rent/mortgage, being evicted, or inability to pay utilities in the past 12 months in adulthood (ages 26–32). Multivariate models demonstrated that the higher number of adverse experiences in childhood, the higher the odds of experiencing housing insecurity in adulthood, controlling for demographic and other factors. In the multivariate model testing the relationship of individual types of adverse experiences, only childhood emotional abuse remained significantly related to higher likelihood of housing insecurity in adulthood after controlling for multiple comparisons. Compared with those who experienced no emotional abuse in childhood, those who reported that they experienced emotional abuse more than ten times in their childhood had approximately 39% higher odds (OR = 1.39, p < 0.01) of experiencing housing insecurity in adulthood. The salience of emotional abuse for increased housing insecurity should receive greater attention in both the housing and child welfare sectors. Highlights: I explore how childhood adversities relate to housing insecurity in adulthood. More adverse childhood events relate to higher odds of adult housing insecurity. Chronic childhood emotional abuse relates to higher odds of adult housing insecurity. Emotional abuse needs more attention in both the housing and child welfare sectors.